Mathematical model of fibre optical converter of gas concentration - Yaremchuk, V. F.; Kravchuk, N. S.; Smishnyi, S. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The results of calculation of basic characteristics of fiber optical sensor of gas concentration, which uses the principle of differential optical radiation absorption and principle of optical absorption method in the range of different wavelengths depending on the parameters of the components used are presented. Basic principles of construction and operation of fiber-optical measuring system, intended for monitoring of ecological environment state are considered.